PENGARUH LITERASI KEUANGAN, LINGKUNGAN SOSIAL, LOCUS OF CONTROL DAN GAYA HIDUP TERHADAP KEMAMPUAN PENGELOLAAN KEUANGAN PADA MAHASISWA AKUNTANSI UNIVERSITAS PRIMA INDONESIA - Sinaga, Novi k.; Lestari , Tya Utami; Br Sinaga, Jholant Bringg Luck Amelia; Siregar , Muhammad Raja (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of Financial Literacy, Social Environment, Locus of Control, and Lifestyle on the Financial Management Ability of Accounting Study Program Students at Prima Indonesia University in 2025. This study uses quantitative methods. The data used in this study are primary data obtained from filling out questionnaires conducted by respondents. The population of this study was 961 students in the 3rd semester and above who were registered in the Accounting Study Program at Prima Indonesia University in 2025. The sample used was 91 students of the Accounting Study Program at Prima Indonesia University using a non-probability sampling technique, namely purposive sampling, with the criteria of active students from the Accounting Study Program at Prima Indonesia University and at least in the 3rd semester. Data analysis used the data instrument test method, classical assumption test, multiple regression analysis test, hypothesis test with the help of the IBM SPSS Statistic 25 program. The results of this study using a partial test (T Test) stated that Financial Literacy and Locus of Control had a positive and significant effect on student Financial Management. Meanwhile, Social Environment and Lifestyle were not proven to have a significant effect on accounting students' Financial Management. Simultaneously (F-test), all independent variables significantly influenced student financial management. This study indicates that improving financial literacy and strengthening self-control are important factors in improving student financial management. Furthermore, the influence of the social environment and lifestyle also needs to be considered in developing better financial management.